2019
DOI: 10.1186/s11658-019-0138-0
|View full text |Cite
|
Sign up to set email alerts
|

The Pro12Ala polymorphism in the PPAR­γ2 gene is not associated with an increased risk of NAFLD in Iranian patients with type 2 diabetes mellitus

Abstract: BackgroundThe peroxisome proliferator-activated receptors (PPARs) are ligand-activated transcription factors that belong to the nuclear hormone receptor superfamily. Several studies have demonstrated a significant association between Pro12Ala polymorphism of the PPAR­γ2 gene and metabolic disorders. Therefore, this study aimed to evaluate the association of Pro12Ala polymorphism with increased risk of NAFLD in Iranian patients with type 2 diabetes mellitus.MethodsThis cross-sectional study was performed on 145… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Nonalcoholic fatty liver disease (NAFLD) is one of the most common forms of chronic liver disorder in developed countries, and it affects more than 70% of patients with type 2 diabetes mellitus and people suffering from obesity [1,2]. NAFLD is characterized by hepatic and systemic insulin resistance, dyslipidemia, and persistent abnormalities in the liver enzymes [3][4][5]. NAFLD comprises a broad spectrum of disease severity, ranging from benign hepatocellular steatosis to nonalcoholic steatohepatitis (NASH-fatty changes with inflammation and hepatocellular damages), advanced liver cirrhosis, hepatocellular carcinoma, and increased risk of liver-related mortalities [6].…”
Section: Introductionmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) is one of the most common forms of chronic liver disorder in developed countries, and it affects more than 70% of patients with type 2 diabetes mellitus and people suffering from obesity [1,2]. NAFLD is characterized by hepatic and systemic insulin resistance, dyslipidemia, and persistent abnormalities in the liver enzymes [3][4][5]. NAFLD comprises a broad spectrum of disease severity, ranging from benign hepatocellular steatosis to nonalcoholic steatohepatitis (NASH-fatty changes with inflammation and hepatocellular damages), advanced liver cirrhosis, hepatocellular carcinoma, and increased risk of liver-related mortalities [6].…”
Section: Introductionmentioning
confidence: 99%
“…PPARγ2 (peroxisome proliferator-activated receptorgamma 2) is a ligand-activated transcription factor of the nuclear hormone receptor superfamily. 187 The PPARγ2 gene plays roles in glucose homeostasis, lipid metabolism, obesity, insulin sensitivity, T2DM, and various adipocytespecific genes. 59,[188][189][190] Based on several case-control and family-based studies, estimated that Pro12 allele (ie, the major allele) of PPARγ was associated with a 1.25-fold elevated risk of T2DM.…”
Section: Pparγ2mentioning
confidence: 99%
“…Increasing experimental studies have investigated the relationship between Pro12Ala polymorphism of PPARγ2 gene and various diseases such as T2DM, insulin sensitivity, obesity, cardiovascular diseases, Alzheimer's disease, and cancer [ 3 ]. Nonalcoholic fatty liver disease (NAFLD) is a progressive liver disease that is determined by dyslipidemia, obesity, hypertension, hypercholesterolemia, type 2 diabetes mellitus, cirrhosis, liver failure, insulin resistance, and hepatocellular carcinoma [ 9 ]. Several researchers reported that Pro12Ala polymorphism was significantly associated with NAFLD [ 10 13 ] in different populations.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have also shown which PPAR γ 2 Pro12Ala polymorphism was associated with CAD [ 8 , 14 ]. Saremi et al found PPAR γ 2 (c.34G>C, Pro12Ala) is considerably associated with higher risk NAFLD [ 9 ] in T2DM patients in Iranian population. These findings suggest a high possibility of involvement of Pro12Ala polymorphism in the risk for CAD, NAFLD, and T2DM.…”
Section: Introductionmentioning
confidence: 99%